Daya Kapilaritas Berbagai Jenis Sumbu pada Sistem Wick - Rachman, Filia Nur (Pendidikan Fisika Universitas Nurul Huda, 2025)
The wick hydroponic system relies heavily on the wick as a medium for delivering nutrient solution to the surface of the flannel cloth used as the growing medium, and selecting a wick with good capillarity is an important factor in supporting optimal plant growth. The wick system is a hydroponic method that enables continuous distribution of nutrient solution with relatively easy maintenance and simple operation. This study aims to analyze and evaluate the capillarity characteristics of several types of wicks through measurements of resistance and absorption capability using an Arduino Nano V3, a digital multimeter, and observation sheets. The data were analyzed using Microsoft Excel for initial processing. The results show that acrylic flannel has higher capillarity and lower resistance compared to polyester flannel, making it more effective in continuously delivering nutrient solution. These findings provide a scientific basis for selecting the optimal wick material in wick hydroponic systems. Future research is recommended to examine a wider variety of wick materials and to conduct direct testing on plant growth to obtain a more comprehensive understanding of wick performance